Cataract surgery and intraocular pressure: perspective from the developing world - Bali, Shaveta; Nawaz, Shah; Mehdi, Manzoor (International Journal of Research in Medical Sciences, 2020)
Background: Cataract surgery has an IOP lowering effect. Aim of the study was to analyses and evaluate the effect of cataract surgery [phacoemulsification] for senile cataract on IOP. Methods: This prospective observational study was carried out at two private specialized ophthalmology centers at India over a period of one year from Jan 2015 to Dec 2015. Cataract surgery (phacoemulsification) was performed on single eye of all the test subjects presenting to the out-patient departments with senile cataract without any comorbidity. Preoperative intraocular pressure (IOP) readings were noted and then compared to the post-operative IOP readings. All the data was collected and analyzed. Results: Cataract surgery reduced the IOP by a mean of 1.6 mmHg. Eyes with a higher preoperative IOP had a much greater IOP reduction post cataract surgery. Patients having a shorter axial length had more IOP reduction after cataract surgery with a mean value of 2.4 mmHg, which was statistically significant with a p value of 0.02. Older patients had a greater decrease in IOP after cataract surgery and it was noted that the relationship between IOP and increasing age was statistically significant having a p value of 0.001. Conclusions: Cataract surgery (phacoemulsification) has a significant IOP lowering effect and it is more in eyes having higher pre-operative IOP, shallower anterior chamber and those of the elderly.